Investigating the genetic association of mitochondrial DNA copy number with neurodegenerative diseases - Huan Xia; Zi-Hao Wang; Xiao-Bei Wang; Mei-Rong Gao; Sen Jiang; Xin-Yu Du; Xin-Ling Yang (BMC Neurology)
Abstract Objective This study aims to investigate the causal relationship between Mitochondrial DNA (mtDNA) copy number and several common neurodegenerative diseases (NDs). Methods We conducted a bidirectional two-sample Mendelian randomization (MR) analysis using data from genome-wide association studies (GWAS) as instrumental variables (IVs). After screening for relevance and potential confounders, we estimated the association between mtDNA copy number and NDs, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Amyotrophic lateral sclerosis (ALS), and Multiple sclerosis (MS). Additionally, we validated our findings using GWAS data on mtDNA copy number from Longchamps et al., sourced from the Genetics Epidemiology Consortium and the UK Biobank (UKB) aging study cohort. Results A GWAS analysis of 395,718 UKB participants found no significant association between mtDNA copy number and the risk of NDs, including AD (OR = 0.956, P = 0.708), PD (OR = 1.223, P = 0.179), ALS (OR = 0.972, P = 0.374), and MS (OR = 0.932, P = 0.789). Similarly, reverse MR analysis revealed no significant relationship between genetic predictions of NDs and mtDNA copy number: AD (OR = 0.987, P = 0.062), PD (OR = 0.997, P = 0.514), ALS (OR = 0.974, P = 0.706), and MS (OR = 1.003, P = 0.181). Conclusion Although mitochondrial dysfunction is implicated in the pathogenesis of NDs, no clear evidence supports a causal role for mtDNA copy number. The relationship between mtDNA copy number and NDs is likely mediated by more complex molecular regulatory mechanisms. Further research is required to elucidate these intricate interactions.